Can There Be Trust After a History of Colonialism and Exploitation? Award of the 2022 Nayacakalou Medal - Pereira, Pandora Fulimalo (Waka Kuaka, 2023)
Pandora Fulimalo Pereira is the esteemed recipient of the 2022 Nayacakalou Medal, given for outstanding contribution to Pacific research and named after the late Dr Rusiate Nayacakalou (1927–1972). Dr Andrea Low, in her introduction of Fuli at the medal ceremony, referred to Fuli as “an innovator, advocate and champion for Pacific peoples and their treasures at Auckland Museum”. Andrea highlighted Fuli’s “singularity and leadership in developing and supporting radical Pacific methodologies”, emphasising Fuli’s national and international esteem as well as her impact as a role model and mentor in developing emerging Pacific museologists. This is a version of the talk that Fuli gave at the medal ceremony on her career and experiences as a Pacific curator in Aotearoa New Zealand.